Driving Fundamentals of Natural Gas Price in Europe - Obadi, Saleh Mothana; Korcek, Matej (International Journal of Energy Economics and Policy, 2020)
This paper attempted to examine the factors driving the price development of the Title Transfer Facility (TTF) month-ahead contract using linear regression over the period 2016–2019 when the TTF market became the most liquid natural gas hub and primary reference source for gas prices in Europe. We examined the possible fundamentals and used OLS methodology to estimate the linear regression model, which explained the development of TTF MA. We concluded the price based on factors determining marginal demand and supply. The most significant factors seemed to be the variables representing the price of German power and the price of coal since the competition between coal and gas in power generation determines the marginal demand, which sets the price for gas. The change in total demand was another significant factor, although its impact was smaller. The significance of the LNG variable indicated the exposure of European natural gas price to the global supply and demand. The model also suggested the importance of storage capacity for the whole system. Keywords: Natural gas price, linear regression, commodity prices, Title Transfer Facility JEL Classifications: Q40, Q42 DOI: https://doi.org/10.32479/ijeep.10192